Consensus active power sharing for islanded microgrids based on distributed angle droop control. Issue 13 (25th May 2021) - Xu, Tao; Zhou, Jiaxin; Liang, Lemeng; Wu, Yuhan; Cai, Shuqi; Liu, Zuozheng; Li, Peng; Yu, Li
Abstract: The implementation of synchronous phasor measurement units (PMUs) in distribution networks provide accurate and GPS‐based synchronous data which support the grid flexible reconfiguration, such as island partition and island reconnection. Utilizing the high resolution PMU data, the phase angle droop control can be implemented on islanded microgrids (MGs) without causing the deviation on frequency brought from traditional frequency droop control, consequently support the synchronous and seamless transition. In this paper, a phase angle droop control method considering the incremental cost of distributed generation (DG) is proposed utilizing distributed finite‐time protocol to realize cost minimization and consensus active power sharing of DG units. In addition, an observer‐based voltage controller with finite‐time convergence velocity is implemented to meet the target of DG units' voltage recovery and the accuracy of reactive power sharing. The proposed method is implemented through a sparse communication topology and exchange information with their own neighbours only. The effectiveness, robustness and scalability of the proposed distributed control method are verified through case studies.